2022
DOI: 10.1002/cjce.24493
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium properties and crystal growth of D2O + cyclopentane hydrate for sustainable tritium separation

Abstract: This study reports thermodynamic properties and crystal growth observations of D 2 O + cyclopentane hydrate toward the development of a hydrate-based tritium separation process. We employed D 2 O as a host of hydrate with respect to the investigation into the formation of D 2 O hydrate substrate, which is a core component of the tritium separation process. The hydrate phase equilibrium temperature in the liquid D 2 O + liquid cyclopentane system was 3.2 C higher than the corresponding H 2 O hydrate. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The dendritic structures created wrinkles on the drop interface along the direction of the front propagation, giving the hydrate film a macroscopically rough appearance (Figure b­(ii)). The transition from polyhedral to dendritic crystals as a function of Δ T sub was also considered by Sakemoto et al and Maruyama and Ohmura for cyclopentane hydrates (Type sII) as well as other formers of sI and sH hydrates. From these studies, it can be concluded that all three types of hydrate structure undergo similar morphological changes at different Δ T sub .…”
Section: Resultsmentioning
confidence: 94%
“…The dendritic structures created wrinkles on the drop interface along the direction of the front propagation, giving the hydrate film a macroscopically rough appearance (Figure b­(ii)). The transition from polyhedral to dendritic crystals as a function of Δ T sub was also considered by Sakemoto et al and Maruyama and Ohmura for cyclopentane hydrates (Type sII) as well as other formers of sI and sH hydrates. From these studies, it can be concluded that all three types of hydrate structure undergo similar morphological changes at different Δ T sub .…”
Section: Resultsmentioning
confidence: 94%
“…Ohmura et al observed the growth of CH 4 hydrate crystals in CH 4 -presaturated liquid water; they revealed that the crystal morphologies of hydrate vary from polyhedral via columnar to dendritic depending on thermodynamic conditions. Since then, the crystal growth of hydrates formed using various guest compounds has been experimentally examined to systematically classify their dynamics and morphology depending on the driving force. As a first example of D 2 O-based hydrate, Maruyama and Ohmura performed crystal growth observation of cyclopentane + D 2 O hydrate and summarized the variation in the morphology of hydrate formed at the D 2 O-cyclopentane interface. Owing to uninflammability, nontoxicity, and accessibility for industrial use, CO 2 is considered to be a promising option for guest compounds compared to other candidates tested in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Truong‐Lam et al [ 15 ] describe the thermodynamic stability, kinetic behaviour, and effectiveness of a water desalination/purification process that is based on the use of tetra‐ or penta‐fluoroethane gas hydrates. Maruyama and Ohmura [ 16 ] explore the design implications of their thermodynamic and crystal growth results for a hydrate‐based isotopic water separation process. Bollineni and Daraboina [ 17 ] investigate the use of clathrate formed from tetra‐n‐butyl ammonium chloride (TBAC) and methane for the treatment of produced water from oil and gas operations.…”
mentioning
confidence: 99%